Implementing cloud storage with OpenStack Swift : design, implement, and successfully manage your own cloud storage cluster using the popular OpenStack Swift software /: design, implement, and successfully manage your own cloud storage cluster using the popular OpenStack Swift software. (2014) - Unknown
No abstract available